Effects of non-thermal mobile phone radiation on breast adenocarcinoma cells - Barend Stander; Sumari Marais; Carin Huyser; Zen Fourie; Dariusz Leszczynski; Annie Joubert (South African Journal of Science, 2011)
Mobile phone usage currently exceeds landline communication in Africa. The extent of this usage has raised concerns about the long-term health effects of the ongoing use of mobile phones. To assess the physiological effects of radiation from mobile phones in vitro, MCF-7 breast adenocarcinoma cells were exposed to 2W/kg non-thermal 900-MHz mobile phone radiation. The effects investigated were those on metabolic activity, cell morphology, cell cycle progression, phosphatidylserine (PS) externalisation and the generation of reactive oxygen species and nitrogen species. Statistically insignificant increases in mitochondrial dehydrogenase activity were observed in irradiated cells when compared to controls. Fluorescent detection of F-actin demonstrated an increase in F-actin stress fibre formation in irradiated MCF-7 cells. Cell cycle progression revealed no statistically significant variation. A small increase in early and late apoptotic events in irradiated MCF-7 cells was observed. No statistically significant changes were observed in reactive oxygen and reactive nitrogen species generation. In addition, quantitative and qualitative analyses of cell cycle activity and nuclear and cytosolic changes, respectively, revealed no significant changes. In conclusion, exposure to 1 h of 900-MHz irradiation induced an increase in PS externalisation and an increase in the formation of F-actin stress fibres in MCF-7 cells. Data obtained from this study, and their correlation with other studies, provides intriguing links between radio frequency radiation and cellular events and warrant further investigation.